A new Keynesian theory of inflation and growth in the long run - Andrea Vaona (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2007)
This paper explores the influence of inflation on economic growth. In order to match the empirical stylized fact of a threshold level of inflation, beyond which inflation ceases to have a positive impact on growth and begins to harm it, we propose to merge an endogenous growth model of learning by doing with a New Keynesian one with sticky wages. In this way, we mimic the stylized fact of a hump shaped relationship between inflation and economic growth.
Keywords: 330